2005
DOI: 10.1002/mar.20095
|View full text |Cite
|
Sign up to set email alerts
|

The relationships among family and social interaction, loneliness, mall shopping motivation, and mall spending of older consumers

Abstract: The study implemented 419 mall-intercept interviews with people who are 55 or older in large malls in three metropolitan cities in the United States. The five subdimensions of mall-shopping motivation of older consumers were identified under two dimensions: Consumption-oriented mall-shopping motivation (service consumption, value consumption, and eating) and experiential mall-shopping motivation (diversion and aesthetic appreciation). The structural model revealed significant effects of social interaction, lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
108
2
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(119 citation statements)
references
References 34 publications
6
108
2
1
Order By: Relevance
“…Another factor that could explain this difference is shopping alone versus with family members and/or friends. The social aspect of shopping is important to consumers' evaluation of the shopping experience (e.g., Kim et al 2005) and therefore might also affect consumers' response to store-induced stress. Our field quasiexperiment did not differentiate between shopping alone vs. with other individuals, which might explain the differences in response.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Another factor that could explain this difference is shopping alone versus with family members and/or friends. The social aspect of shopping is important to consumers' evaluation of the shopping experience (e.g., Kim et al 2005) and therefore might also affect consumers' response to store-induced stress. Our field quasiexperiment did not differentiate between shopping alone vs. with other individuals, which might explain the differences in response.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Amongst older shoppers this is of specific interest, as past research has shown that the sociality of the shopping experience is more prevalent for those people of an older age, particularly those living alone and therefore seeking social interaction to overcome loneliness and boredom, and fulfilling other benefits such as taking exercise and getting a change of scenery (e.g. Kim et al, 2005: Myers and Lumbers, 2008: Sudbury and Simcock, 2009). …”
Section: Implications For Researchmentioning
confidence: 99%
“…It is therefore imperative for the retailers and mall managers to make shopping an entertaining experience. While differentiating their outlets from those of their competitors, this would lead to increase in footfalls at their malls (Kim, Jikeyong and Minsung, 2005;Talmadge, 1995).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Holbrook and Hirschman (1982) argued that just information processing is not sufficient; they proposed a model accommodating different experiential variables that focuses on the symbolic, hedonic, and aesthetic nature of consumption. Kim et al (2005) classified experiential shopping constituting of utilitarian and hedonic factors.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation